Image Semiotics in the Book Our Arabic Language for the Third Grade in Jordan: An Analytical Study Using Human and Artificial Intelligence - Bani Omar, Khitam Ahmad (European Scientific Journal, ESJ, 2023)
The current study aimed to identify the image semiotics in the textbook our Arabic Language for the third grade in Jordan using human intelligence and artificial intelligence. To achieve the study objectives, the content and semiotic analysis method was adopted using human intelligence and artificial intelligence. The study sample consisted of the entire study population represented in the images of the textbook our Arabic language for the third grade which consisted of (20) images. The most prominent results revealed a male bias in terms of the number of characters, functional roles, social roles, talents and activities, and there was a convergence between the semiotic analysis using human intellence and semiotic analysis using artificial intelligence. The results also showed that there were differences in the results of the semiotic analysis between the analysis using artificial intelligence and the use of artificial intelligence, as the human analysis connects images with social context and other images, while the artificial intelligence deals with every image separately.